2023
DOI: 10.1007/s10546-023-00790-5
|View full text |Cite
|
Sign up to set email alerts
|

Midday Boundary-Layer Collapse in the Altiplano Desert: The Combined Effect of Advection and Subsidence

Abstract: Observations in the Altiplano region of the Atacama Desert show that the atmospheric boundary layer (ABL) suddenly collapses at noon. This rapid decrease occurs simultaneously to the entrance of a thermally driven, regional flow that causes a rise in wind speed and a marked temperature decrease. We identify the main drivers that cause the observed ABL collapse by using a land–atmosphere model. The free atmosphere lapse rate and regional forcings, such as advection of mass and cold air as well as subsidence, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Nonetheless, small wetlands surrounded by desertic conditions-such as those reviewed in this study-are subject to advection. Recent investigations performed in the Altiplano region have shown that advection enhances open water evaporation and results in sudden boundary-layer collapses in the desert (Aguirre-Correa et al, 2023;Lobos-Roco et al, 2021;Su arez et al, 2020). Therefore, the estimated evapotranspiration values are likely to be underestimated due to advection processes.…”
Section: Precipitation Snow Characterization and Evapotranspiration E...mentioning
confidence: 99%
“…Nonetheless, small wetlands surrounded by desertic conditions-such as those reviewed in this study-are subject to advection. Recent investigations performed in the Altiplano region have shown that advection enhances open water evaporation and results in sudden boundary-layer collapses in the desert (Aguirre-Correa et al, 2023;Lobos-Roco et al, 2021;Su arez et al, 2020). Therefore, the estimated evapotranspiration values are likely to be underestimated due to advection processes.…”
Section: Precipitation Snow Characterization and Evapotranspiration E...mentioning
confidence: 99%